2011
DOI: 10.1159/000330413
|View full text |Cite
|
Sign up to set email alerts
|

Is Octreotide Treatment Useful in Patients with Congenital Chylothorax?

Abstract: Background: Congenital chylothorax (CC) is a severe congenital disorder characterized by the collection of chyle in the pleural space. Recent case reports suggest that the use of octreotide in the treatment of CC may be useful. Objective: To evaluate the effect of octreotide on pleural effusions in CC. Methods: Hospital records of 7 patients with a CC, who were admitted to the Neonatal Intensive Care Unit of the Radboud University Nijmegen Medical Centre between 2006 and 2010 and were treated with octreotide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
0
23
0
1
Order By: Relevance
“…Enteral nutrition with medium-chain triglycerides and total parenteral nutrition have been successfully employed. In this case, the parenteral nutrition was not possible due to shortage in the pharmacy of the hospital [10] [11].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Enteral nutrition with medium-chain triglycerides and total parenteral nutrition have been successfully employed. In this case, the parenteral nutrition was not possible due to shortage in the pharmacy of the hospital [10] [11].…”
Section: Discussionmentioning
confidence: 98%
“…Nutrition plays an important role in reducing lymphatic production [10]. Enteral nutrition with medium-chain triglycerides and total parenteral nutrition have been successfully employed.…”
Section: Discussionmentioning
confidence: 99%
“…No practice recommendation was made based on this evidence. Horvers et al 124 reported on the use of octreotide in 7 patients with congenital chylothorax. Pleural effusions eventually decreased in all patients after administration of 5 to 6 mg octreotide/kg per minute, but the authors felt that the decrease might reflect the natural history of congenital chylothorax and, hence, no clear, consistent effect of octreotide was identified.…”
Section: Figurementioning
confidence: 99%
“…A randomized, controlled, multicenter trial is needed to assess the safety and efficacy of octreotide and somatostatin use in the treatment of chylothorax in children. 123,124 Other agents used in the treatment of chylothorax include nitric oxide and etilefrine. A case report described the use of nitric oxide in a neonate who developed a chylothorax after surgery for congenital heart disease.…”
Section: Figurementioning
confidence: 99%
“…Given subcutaneously or intravenously it is thought to have a direct effect on the vascular somatostatin receptor level with vasoconstriction of the splanchnic circulation, thereby decreasing chyle production, intestinal lymphatic volume and flow in the thoracic duct [60]. Treatment trials with Octreotide for patients with CPL and CC are only reported in uncontrolled case studies [41,[60][61][62] with no clear and consistent effect on pleural effusions. Adverse side effects like gastrointestinal intolerance or transient hypothyroidism have to be considered.…”
Section: Therapeutic Optionsmentioning
confidence: 99%